Final Disposal of Ashes from Sunflower Husk in Cementitious Mortars - Señas, Lilia (2012)
This paper presents the study of the behavior of cementitious mortars with incorporated ashes produced during the incineration process of sunflower husk in boiler. For ash characterization, the chemical composition of majority and minority elements was determined by Inductively Coupled Plasma Mass Spectroscopy (ICP), the crystalline structure by X-ray diffraction (XRD), and the optical properties by petrographic microscopy. Two different groups of mortars were elaborated. In one of them fluidity of the mixture was maintained constant throughout the study, and in the other, the w/c ratio. Proportions of incorporated ashes were 5 %, 10 % and 15 % compared with the weight of the cement used. As the rate of incorporated ashes increased, the fluidity of the mixture and the setting time changed compared with those of the control mortar. The flexural strength and the compressive strength were determined at the age of 7 and 28 days. Both parameters decreased compared with those of the control as the percentage of incorporated ashes increased. A petrographic study of thin sections of the mortars was conducted using a petrographic microscope. No textural or compositional changes were observed at microscopic level in the different mixtures studied.